2023
DOI: 10.1002/anie.202305239
|View full text |Cite
|
Sign up to set email alerts
|

New Anderson‐Based Polyoxometalate Covalent Organic Frameworks as Electrodes for Energy Storage Boosted Through Keto‐Enol Tautomerization

Abstract: The unique electrochemical properties of polyoxometalates (POMs) render them ideal components for the fabrication of next‐generation high‐performance energy storage systems. However, their practical applications have been hindered by their high solubility in common electrolytes. This problem can be overcome by the effective hybridization of POMs with other materials. Here we present the design and synthesis of two novel polyoxometalate‐covalent organic frameworks (POCOF) via one‐pot solvothermal strategy betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Up to now, COFs have great potential for various applications, including gas adsorption and separation, sensing, heterogeneous catalysis, energy storage and other aspects. 32–39 Furthermore, numerous research findings have indicated that two-dimensional (2D) COFs possess excellent semiconductor properties and are a new type of superior photocatalysts, particularly for hydrogen generation via water splitting. As metal-free semiconductor photocatalysts, the advantages of 2D-COFs can be described as follows: first, one-dimensional nanopores with large surface area provide space for transport, action and transformation of matter, and also increase exciton utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, COFs have great potential for various applications, including gas adsorption and separation, sensing, heterogeneous catalysis, energy storage and other aspects. 32–39 Furthermore, numerous research findings have indicated that two-dimensional (2D) COFs possess excellent semiconductor properties and are a new type of superior photocatalysts, particularly for hydrogen generation via water splitting. As metal-free semiconductor photocatalysts, the advantages of 2D-COFs can be described as follows: first, one-dimensional nanopores with large surface area provide space for transport, action and transformation of matter, and also increase exciton utilization.…”
Section: Introductionmentioning
confidence: 99%
“…108 Ciesielski and co-workers synthesized two polyoxometalate–covalent organic frameworks (POCOF) by condensation reaction between H 2 N–(CoMo 6 )–NH 2 and two different aldehyde building blocks (benzene-1,3,5-tricarbaldehyde (BTC) and 2,4,6-triformylphloroglucinol (TFP)) respectively through one-pot solvothermal strategy. 109…”
Section: Cof–pom Hybrid Materialsmentioning
confidence: 99%
“…In addition, POCOF-1 and POCOF-2 presented greater cyclability with a capacitance retention of 90% and 74% 5000 GCD cycles. 109…”
Section: Cof–pom Hybrid Materialsmentioning
confidence: 99%
“…One approach to this end is the use of organo‐functionalized POMs (organoPOMs) where the metal oxo cluster shell has been covalently functionalized with organic moieties [9–11] . Organo‐functionalization provides control over the physical and electronic structure of the POMs, making them ideal building blocks for supramolecular assemblies [12–14] .…”
Section: Introductionmentioning
confidence: 99%
“…One approach to this end is the use of organofunctionalized POMs (organoPOMs) where the metal oxo cluster shell has been covalently functionalized with organic moieties. [9][10][11] Organo-functionalization provides control over the physical and electronic structure of the POMs, making them ideal building blocks for supramolecular assemblies. [12][13][14] Thus organoPOMs have successfully been employed as molecular components in the assembly of functional supramolecular systems with unique functions.…”
Section: Introductionmentioning
confidence: 99%